Non-cytotoxic functions of CD8 T cells: “repentance of a serial killer” - Al Moussawy, Mouhamad; Abdelsamed, Hossam A. (Frontiers in Immunology, 2022)
Cytotoxic CD8 T cells (CTLs) are classically described as the “serial killers” of the immune system, where they play a pivotal role in protective immunity against a wide spectrum of pathogens and tumors. Ironically, they are critical drivers of transplant rejection and autoimmune diseases, a scenario very similar to the famous novel “The strange case of Dr. Jekyll and Mr. Hyde”. Until recently, it has not been well-appreciated whether CTLs can also acquire non-cytotoxic functions in health and disease. Several investigations into this question revealed their non-cytotoxic functions through interactions with various immune and non-immune cells. In this review, we will establish a new classification for CD8 T cell functions including cytotoxic and non-cytotoxic. Further, we will discuss this novel concept and speculate on how these functions could contribute to homeostasis of the immune system as well as immunological responses in transplantation, cancer, and autoimmune diseases.